Cinema as a Political Media Germany and Italy Compared, 1945-1950s - Zimmermann, Clemens; Klinkhammer, Lutz (Online-Schriften des DHI Rom. Neue Reihe; Pubblicazioni online del DHI Roma. Nuova serie, 2021)
Based on a comparative, transnational approach, the international group of authors focuses on the respective national interpretations of the past in Germany and Italy, as presented in the medium of film between 1945 and around 1955, and also addresses the mutual perception of the films. In the 12 contributions, both the filmic narrative patterns of important individual works are analyzed and the contemporary context of the debate about the horrors and trauma of the National Socialist and Fascist past in both countries is included.